Twitter mood light - Kwa, Kah Yee (2014)
Throughout the years, social media have been evolving and gaining worldwide popularity rapidly. It has become an important aspect for social networking and content sharing online. Twitter, an online social networking service, commands more than 650 million registered users. It is one of the fastest growing social networking service to date, generating millions of content that can be used to as a tell-tale of the world events.